Pengaruh Motivasi Belajar Terhadap Kemampuan Membaca Alquran Santri MDTA IKRAR Tungka Kec. Patamuan Kab. Padang Pariaman - Murdiana Murdiana; Iswantir M; Charles Charles; Arifmiboy Arifmiboy (KOLONI, 2022)
This research is motivated by the existence of students if they learn to like to play, do not pay attention to the teacher when explaining, rarely do the assignments given, students' low knowledge of tajwid and lazy in learning. This study aims to describe: (1) Learning Motivation of MDTA IKRAR Tungka Santri Kec. Patamuan Kab. Padang Pariaman, (2) Ability to Read the Qur'an of MDTA IKRAR Tungka Santri Kec. Patamuan Kab. Padang Pariaman, (3) The Influence of Learning Motivation on the Ability to Read the Qur'an of MDTA IKRAR Tungka Santri Kec. Patamuan Kab. Pariaman Padang. This study uses a quantitative approach with a correlational type. Sampling using total sampling technique. And the sample in this study were 35 students. With data collection techniques in the form of questionnaires and tests. The analysis technique uses the formula r product moment, correlation coefficient, and coefficient of determination. While the requirements for the analysis test used normality, linearity and homogeneity tests. The results of the study are: (1) The results of the study of students' learning motivation are in the low category with a percentage of 35%. (2) The results of the research on the ability to read the Koran of students are in the medium category with a percentage of 54%. While the results of the research on the influence of learning motivation on the ability to read the Koran of students obtained the results of 0.439. (3) The results of the determination test obtained x 100% = 19%. So the ability to read the Koran 19% is influenced by learning motivation, the remaining 81% is influenced by other factors not examined in this study.  Keywords: Learning Motivation, Ability to Read Al-Quran, MDTA